Catastrophe Risk Management : Using Alternative Risk Financing and Insurance Pooling Mechanisms - Pollner, John D. (World Bank, Washington, DC, 2014)
Residual stochastic risks from catastrophic natural events can be addressed through insurance pooling and risk transfer mechanisms that provide the basis for financial protection and instill strong incentives for reducing vulnerability. To reduce the economic stress after disasters, the author shows, World Bank instruments could be used to support initiaitves to help correct market imperfections in catastrophe insurance. He takes a step-by-step approach to showing how both risk pooling structures and alternative catastrophe coverage mechanisms (long-maturity risk financing facilities, weather-indexed contracts, and capital market instruments) can achieve better risk protection and financing terms--enough to allow the expansion of insurance coverage of public assets and private property. The author examines the insurable assets (private and public) in eight countries in the easternmost part of the Caribbean and, by quantifying the portion of the premium and risk used to fund catastrophe losses, shows that through pooling and the use of credit-type instruments for catastrophe coverage, governments and uninsured property owners or enterprises (with insurable assets) could expect to improve their terms of coverage. Neither local insurers nor reinsurers would suffer in profitability. The risk management options the author examines could lead to real benefits for all participants (buyers and sellers) in insurance markets. But four factors are essential for ensuring the integrity of any participatory insurance scheme for providing risk management in disaster-prone areas such as the Caribbean: 1) stronger regulatory requirements and supervision in the insurance sector; 2) Broad-based, pooled catastrophe funding structures with efficient risk transfer tools; 3) Public insurance policies linked to programs for loss reduction in uninsured sectors; and 4) Stronger risk assessment and enforcement of such structural measures as zoning and compliance with building codes.